History and prospects of intracytoplasmic sperm injection (ICSI) and the development of golden hamster ICSI embryos - Nami Morishita (Reproductive Medicine and Biology, 2021)
Abstract Background Golden (Syrian) hamsters have many advantages for the study of reproductive biology and developmental biology, including a consistent estrous cycle, a stable superovulation response, and a short gestation period. However, there are serious difficulties in doing in vitro manipulations of hamster embryos, because they are very sensitive to various environmental factors. Thus, biotechnological researches of hamster embryos should be performed with high‐level skills of embryo manipulations. Methods The authors summarized the history of hamster intracytoplasmic sperm injection (ICSI) and introduced key points for hamster ICSI, which were found in our previous studies on the production of embryos by ICSI and offspring by embryo transfer. Main findings The key points for hamster ICSI were in vitro manipulations under the light‐controlled environment, injection of acrosome‐less sperm heads into oocytes as soon as possible before spontaneous oocyte activation occurs, and determination of the optimal culture conditions. Conclusion To our knowledge, there are no available reports on production of offspring from ICSI embryos in hamsters except our reports. Moreover, success rates of hamster ICSI remain very low. For the purpose of spreading hamster ICSI, it is necessary to make further researches to improve manipulation techniques and to resolve experimental problems.